Repetition, Communication, and Meaning in the Ancient World : Orality and Literacy in the Ancient World, vol. 13 - Beck, Deborah, (Mnemosyne, Supplements ;, 2021)
This edited volume, arising from the 2019 conference "Orality and Literacy: Repetition," explores some of the many forms and uses of repetition, in poetry, philosophy, and inscriptions, from Homeric epic through the Latin novel and the Gospels to reception in the twentieth century. All human communication depends on repeating signs that are comprehensible to the speaker and the addressee. Yet "repetition" takes many specific forms, in different performance contexts, time periods, and literary genres. Repetition may operate within one utterance, or across several times, places, and artists. The relationship between two repeated utterances cannot always be determined with certainty. But repetition offers exciting ways to understand the communicative process in oral and literate contexts across the ancient world.